Exploring the impact of the COVID-19 pandemic and UK lockdown on individuals with experience of eating disorders - Dawn Branley-Bell; Catherine V. Talbot (Journal of Eating Disorders, 2020)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic may raise unique challenges for individuals with experience of eating disorders. Many factors have potential for detrimental impacts on psychological wellbeing and eating disorder recovery, including: Disruption to living situations, ‘social distancing’ restrictions, difficult access to healthcare, and societal changes to food behaviours and technology usage. To date, little is known on the impact of the pandemic on this population, particularly within the UK. Method A mixed-methods online survey was developed for the purpose of this study. Data was collected from 129 individuals currently experiencing, or in recovery from, an eating disorder during the early stages of the UK pandemic lockdown. Participants were aged between 16 and 65 years, with 121 participants identifying as female, 7 male and 1 participant preferring not to disclose their gender. Results Findings suggest that the pandemic is having a profound, negative impact upon individuals with experience of eating disorders. Eight key themes were generated: Disruption to living situation, increased social isolation and reduced access to usual support networks, changes to physical activity rates, reduced access to healthcare services, disruption to routine and perceived control, changes to relationship with food, increased exposure to triggering messages, and positive outcomes. The results suggest detrimental impacts on psychological wellbeing including decreased feelings of control, increased feelings of social isolation, increased rumination about disordered eating, and low feelings of social support. Conclusions Individuals with eating disorders are at significant risk of negative impacts of the pandemic. There is a vital need for interventions to support this population. Inequalities in healthcare provision were identified, emphasising a need for a more cohesive approach to remote treatment across UK healthcare services. Positive aspects of technology use were identified but the results suggest a need to address and/or limit the potential for negative impacts of public messages around food and exercise behaviours, and to co-design technologies with end-users to facilitate effective treatment.